Pengaruh Brand Awareness, Kualitas Produk dan Harga Terhadap Keputusan Pembelian MCCafe - Cindy Andriani; Vina Meliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study to understand the effect of brand awareness, product quality and price towards the purchase decision of McCafe coffee.This study uses a quantitative approach. Data was collected by distributing questionnaires using a Likert scale to measure each statement. Samples were taken as many as 160 respondents using non- probability sampling method with the kriteria that knows then consume McCafe coffee and this research uses validity test, reliability test, classic assumption test, multiple linear regression and hypothesis test with the help of SPSS 20 program. The result of this hipotesis test shows that brand awareness has effect to purchase decision, product quality has effect to purchasing decision, price has effect to purchase decision, and also simultaneously brand awareness, product quality and price on purchase decision at McCafe.